1986
DOI: 10.1099/00221287-132-7-2057
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Nutrient Gradients in a Bacterial Colony

Abstract: 2057Oxygen and substrate gradients were simulated with a finite-volume method for a variety of bacterial colony sizes and substrate concentrations. A spherical segment geometry and a Monod relationship for simultaneous substrate and O2 consumption were assumed. The results agreed well with previous theoretical and experimental estimates for gradients in microbial colonies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Fraleigh & Bungay (1986) have simulated O2 and substrate gradients as a first step in obtaining a detailed colony growth model. Despite major simplifications in the definition of the colony system the model yielded results which were similar to those from microelectrode studies.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…Fraleigh & Bungay (1986) have simulated O2 and substrate gradients as a first step in obtaining a detailed colony growth model. Despite major simplifications in the definition of the colony system the model yielded results which were similar to those from microelectrode studies.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…Oxygen profiles in colonies and in the solid medium have been measured using microelectrodes (Wimpenny & Coombs, 1983;Bungay et al, 1983;Peters et al, 1987). Fraleigh & Bungay (1986) modelled oxygen and substrate gradients in the colony. Wimpenny (1979) found that near the periphery or leading edge of a growing colony, the height rises relatively steeply to a ridge.…”
Section: Introductionmentioning
confidence: 99%
“…In spatially constrained cell populations the shape of the growth profile depends both upon the biochemical environment and mechanical constraints (Andersen and von Meyenburg, 1980 ; Matsushita and Fujikawa, 1990 ; Tuson et al, 2012 ; Farrell et al, 2013 ; Rudge et al, 2013 ; Smith et al, 2017 ; Winkle et al, 2018 ). At the typical bacterial microcolony scale the biochemical environment is essentially uniform in space due to the fast diffusion of small molecules like sugars and aminoacids (Matson and Characklis, 1976 ; Fraleigh and Bungay, 1986 ; Guélon et al, 2012 ). Using microfluidic devices cells can be maintained in constant fresh media allowing observation of the long term dynamics of genetic circuits (Danino et al, 2010 ; Long et al, 2013 ; Potvin-Trottier et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%